Patient‐Reported Outcomes Measurement Information System Tools for Collecting Patient‐Reported Outcomes in Children With Juvenile Arthritis. Issue 3 (March 2017) - Brandon, Timothy G.; Becker, Brandon D.; Bevans, Katherine B.; Weiss, Pamela F.
Abstract : Objective: To evaluate the precision and construct validity of pediatric Patient‐Reported Outcomes Measurement Information System( PROMIS) instruments in a population of juvenile idiopathic arthritis (JIA) patients and parent proxies. Methods: A convenience sample of JIA patients and parents of JIA patients completed PROMIS instruments for 8 domains: anger, anxiety, depressive symptoms, fatigue, mobility, pain interference, peer relationships, and upper‐extremity function. Short form and computerized adaptive test (CAT) scores were derived from item bank responses. Raw scores were translated to standardized T scores with corresponding SEs. Discrimination between inactive versus active disease was evaluated as an indicator of each measure's construct validity. SEs were plotted to evaluate each instrument's relative precision. Patient‐parent concordance was assessed using intraclass correlations (ICCs). Results: A total of 228 patients and 223 parents participated, providing 71–78 responses per domain. Patient‐ and parent‐reported anger, fatigue, mobility, and pain interference scores significantly differed between those with inactive and active disease. Anxiety, depressive symptoms, and peer relationships differed by disease activity levels for parent‐report only. Short forms and CATs provided comparable reliability to the full item banks across the full range of each outcome. Patient‐parent agreement ranged from ICC 0.3 to 0.8. CATs did not reduce the number of items for any domain compared to the short form. Conclusion: Precision and discriminatory abilities of PROMIS instruments depend on health domain and report type (self‐report versus parent proxy‐report) for children with JIA. Varying levels of patient‐parent concordance reinforces the importance of considering both perspectives in comprehensive health outcomes assessments.